VarB: a variation browsing and analysis tool for variants derived from next-generation sequencing data. - Preston, MD; Manske, M; Horner, N; Assefa, S; Campino, S; Auburn, S; Zongo, I; Ouedraogo, J; Nosten, F; Anderson, T; Clark, T (2012)
SUMMARY: There is an immediate need for tools to both analyse and visualize in real-time single-nucleotide polymorphisms, insertions and deletions, and other structural variants from new sequence file formats. We have developed VarB software that can be used to visualize variant call format files in real time, as well as identify regions under balancing selection and informative markers to differentiate user-defined groups (e.g. populations). We demonstrate its utility using sequence data from 50 Plasmodium falciparum isolates comprising two different continents and confirm known signals from genomic regions that contain important antigenic and anti-malarial drug-resistance genes. AVAILABILITY AND IMPLEMENTATION: The C++-based software VarB and user manual are available from www.pathogenseq.org/varb. CONTACT: taane.clark@lshtm.ac.uk